2018
DOI: 10.3390/pharmacy6030097
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorders in Relationship with Dietary Habits among Pharmacy Students in Romania

Abstract: Changing dietary habits of university students is due to personal, social, educational or religious factors. The relationship between dietary habits and presence of eating disorders among university students is less known in Romania. Material and Methods: Ninety-one pharmacy students (91.21% women) were included in the research. Socio-demographic, anthropometric, medical, and psychological data were collected. Dietary self-declared habits were registered. The analysis of data was done using SPSS, v23. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…We suspect that psychological vulnerability of female nurses resulted in dietary restraint. The negative correlations between energy intake and EDI-3 scores observed in the present study are similar to those of Iorga et al, who showed negative associations between several EDI-3 subscale scores and a tendency to skip meals and restrict energy intake in predominantly (>90%) female pharmacy students [51]. The EDI-3 subscale scores of the current study were also similar to those reported by Iorga et al [51].…”
Section: Discussionsupporting
confidence: 91%
“…We suspect that psychological vulnerability of female nurses resulted in dietary restraint. The negative correlations between energy intake and EDI-3 scores observed in the present study are similar to those of Iorga et al, who showed negative associations between several EDI-3 subscale scores and a tendency to skip meals and restrict energy intake in predominantly (>90%) female pharmacy students [51]. The EDI-3 subscale scores of the current study were also similar to those reported by Iorga et al [51].…”
Section: Discussionsupporting
confidence: 91%
“…This practice may have both positive and negative effects on nutritional status, health, and finally on the quality of life. Eating restrictions may lead to unhealthy dietary habits and eating disorders [4]. On the other hand, present-day diets with a high content of fat, sweet, and energy density often correlate with higher body mass index (BMI) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For them, disordered eating behaviors have become so common in Western society that restrictive diets, as well as compensatory and purgative practices, are commonly considered "normal" behaviors. This normalization results in the intensification of behaviors harmful to women's health (Iorga et al, 2018;Batista et al, 2015;Macneill et al, 2017;Talwar, 2012;Yahia et al, 2011).…”
Section: Ohara Et Al (2014)mentioning
confidence: 99%
“…This is corroborated by all the studies included in this review that were conducted with the university population of both genders (57.1%; n=12). These research presented unanimous results regarding the higher prevalence of body dissatisfaction and higher occurrence of risky eating behaviors in women (Alba et al, 2012;Batista et al, 2015;Escolar-Llamazares et al, 2017;González-Carrascosa et al, 2014;Iorga et al, 2018;Macneill et al, 2017;Memon et al, 2012;Nergiz-Unal et al, 2014;Ohara et al, 2014;Vankim et al, 2016;Yahia et al, 2011;Yean et al, 2013).…”
Section: Ohara Et Al (2014)mentioning
confidence: 99%
See 1 more Smart Citation